Species Interaction and Selective Carbon Addition During Antibiotic Exposure Enhances Bacterial Survival - Jackson, Lindsay M. D.; Kroukamp, Otini; Yeung, William C.; Ronan, Evan; Liss, Steven N.; Wolfaardt, Gideon M. (Frontiers in Microbiology, 2019)
Biofilms are multifaceted and robust microbiological systems that enable microorganisms to withstand a multitude of environmental stresses and expand their habitat range. We have shown previously that nutritional status alters antibiotic susceptibility in a mixed-species biofilm. To further elucidate the effects of nutrient addition on inter-species dynamics and whole-biofilm susceptibility to high-dose streptomycin exposures, a CO2 Evolution Measurement System was used to monitor the metabolic activity of early steady state pure-culture and mixed-species biofilms containing Pseudomonas aeruginosa and Stenotrophomonas maltophilia, with and without added carbon. Carbon supplementation was needed for biofilm recovery from high-dose streptomycin exposures when P. aeruginosa was either the dominant community member in a mixed-species biofilm (containing predominantly P. aeruginosa and S. maltophilia) or as a pure culture. In contrast, S. maltophilia biofilms could recover from high-dose streptomycin exposures without the need for carbon addition during antibiotic exposure. Metagenomic analysis revealed that even when inocula were dominated by Pseudomonas, the relative abundance of Stenotrophomonas increased upon biofilm development to ultimately become the dominant species post-streptomycin exposure. The combined metabolic and metagenomic results demonstrated the relevance of inter-species influence on survival, and that nutritional status has a strong influence on the survival of P. aeruginosa dominated biofilms.